DREADD-mediated amygdala activation is sufficient to induce anxiety-like responses in young nonhuman primates - Sascha A.L. Mueller; Jonathan A. Oler; Patrick H. Roseboom; Nakul Aggarwal; Margaux M. Kenwood; Marissa K. Riedel; Victoria R. Elam; Miles E. Olsen; Alexandra H. DiFilippo; Bradley T. Christian; Xing Hu; Adriana Galvan; et al. (Current Research in Neurobiology, 2023)
Anxiety disorders are among the most prevalent psychiatric disorders, with symptoms often beginning early in life. To model the pathophysiology of human pathological anxiety, we utilized Designer Receptors Exclusively Activated by Designer Drugs (DREADDs) in a nonhuman primate model of anxious temperament to selectively increase neuronal activity of the amygdala. Subjects included 10 young rhesus macaques; 5 received bilateral infusions of AAV5-hSyn-HA-hM3Dq into the dorsal amygdala, and 5 served as controls. Subjects underwent behavioral testing in the human intruder paradigm following clozapine or vehicle administration, prior to and following surgery. Behavioral results indicated that clozapine treatment post-surgery increased freezing across different threat-related contexts in hM3Dq subjects. This effect was again observed approximately 1.9 years following surgery, indicating the long-term functional capacity of DREADD-induced neuronal activation. [11C]deschloroclozapine PET imaging demonstrated amygdala hM3Dq-HA specific binding, and immunohistochemistry revealed that hM3Dq-HA expression was most prominent in basolateral nuclei. Electron microscopy confirmed expression was predominantly on neuronal membranes. Together, these data demonstrate that activation of primate amygdala neurons is sufficient to induce increased anxiety-related behaviors, which could serve as a model to investigate pathological anxiety in humans.